2015
DOI: 10.1038/srep09920
|View full text |Cite
|
Sign up to set email alerts
|

Vasectomy and prostate cancer risk: a meta-analysis of cohort studies

Abstract: Some studies have suggested that vasectomy is associated with the increased risk of prostate cancer, however, this conclusion is not supported by all the published studies. In order to examine the relationship between vasectomy and prostate cancer risk, we conducted a meta-analysis of cohort studies to clarify this controversial association. PubMed and Medline were used to identify the cohort studies that reported the association of vasectomy with prostate cancer risk from 1980 to January 2015. Based on a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 27 publications
1
12
0
2
Order By: Relevance
“…Furthermore, concerns have been raised about bias, unmeasured confounding, and chance in relation to the small increased risk found by others 2554 Recently published meta-analyses of these studies found that vasectomy was not associated with risk of prostate cancer,6 7 and guidelines from the American Urological Association in 2012 recommended that clinicians do not need to routinely discuss prostate cancer during preoperative counselling of men considering vasectomy 55…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, concerns have been raised about bias, unmeasured confounding, and chance in relation to the small increased risk found by others 2554 Recently published meta-analyses of these studies found that vasectomy was not associated with risk of prostate cancer,6 7 and guidelines from the American Urological Association in 2012 recommended that clinicians do not need to routinely discuss prostate cancer during preoperative counselling of men considering vasectomy 55…”
Section: Discussionmentioning
confidence: 99%
“…Although vasectomy is a simple process with a high success rate (>99%) and minimal complications (such as swelling and pain), it is still underutilized around the world, especially in developing countries (Cook, Van Vliet, Lopez, Pun, & Gallo, 2014;Mohamad Al-Ali et al, 2014;Rayala & Viera, 2013;Shang et al, 2015). The worldwide rate of vasectomy use is reported at 3%, with a rate of 2% in developed countries (United States Agency 620275J MHXXX10.1177/1557988315620275American Journal of Men's HealthKısa et al…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, recently published studies evaluating the Cancer Prevention Study (CPS)-II cohort and healthcare databases from Ontario, Canada, demonstrated no association between vasectomy and either overall prostate cancer incidence or mortality (13,14). In addition, while it would be anticipated that having a vasectomy at a younger age would result in a longer exposure, and therefore increase the risk of prostate cancer, this has not been demonstrated (15).…”
Section: Introductionmentioning
confidence: 99%